INTERNALISASI NILAI-NILAI DA'WAH DI SEKOLAH TINGGI ILMU DA'WAH MOHAMMAD NATSIR - Subhan, Agung Aditya (2012)
This research aims to determine the process of internalizing the values of da'wah carried on STID Mohammad Natsir, the values of da'wah are instilled, factors that influence it, and how did it go. The approach used is qualitative research using data collection techniques: observation, interviews, and document study. The analysis technique is descriptive analysis. Based on research data have been obtained, it was found that the STID Mohmmad Natsir to internalize the values of da'wah to students covering all aspects of human education. The embedded value is based on the value of faith and values Ittiba 'Al-Rasul. While the factors that influence the success of the internalization of values that do comes from three things, namely, the values that are believed to be a person, from the surrounding environment, and norms prevailing in the guidance. Internalization of this value was quite successful in establishing the character of du'at.